2018
DOI: 10.1016/j.whi.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Rated Access to Needed Care: Patient-Centered Medical Home Principles Intertwined

Abstract: Access, communication, and care coordination are interrelated. Approaches to improving access may prove counterproductive if they compromise the team's ability to coordinate care, or diminish the team's role as a primary point of contact for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…However, the results were mixed in terms of patients' self-reported experiences with access after PCMH implementation. Three studies reported improvements in patients' perceptions of their access to care (Brunner et al, 2018; Christensen et al, 2013; Schuttner et al, 2020). For example, Christensen et al (2013) found that patients within the PCMH scored survey responses regarding access significantly better than those in non-PCMH clinics.…”
Section: Resultsmentioning
confidence: 99%
“…However, the results were mixed in terms of patients' self-reported experiences with access after PCMH implementation. Three studies reported improvements in patients' perceptions of their access to care (Brunner et al, 2018; Christensen et al, 2013; Schuttner et al, 2020). For example, Christensen et al (2013) found that patients within the PCMH scored survey responses regarding access significantly better than those in non-PCMH clinics.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 A recent study from the Veterans Health Administration (VHA) found that the use of telephone communication is strongly associated with higher patient perceptions of access. 4 To our knowledge, no studies have specifically examined rural patients' perceptions of access associated with telephone visits, especially for clinics with longer wait times for in-person visits. Our objective was to examine whether self-reported access to primary care is associated with actual clinic wait times and use of telephone visits, and to assess whether this relationship differs between rural and urban settings.…”
mentioning
confidence: 99%